The Islamic Calligraphy Styles And Scripts In Muslims' Architecture: An Overview - Baydoun, Ziad; Kamaruddin, Zumahiran (WMIT GROUP SDN BHD, 2020)
Islamic calligraphy is one of the most is highly notable by the Islamic civilization. This art is the most prevalent in the countries of the Arabs and Muslims alike. Islamic calligraphy strongly presents in many types of buildings, furniture, and clothes with different styles and scripts. The presence of calligraphy in those objects is not only for an aesthetic purpose but also an essential element, reflecting cultural values. In architecture, for example, in a mosque, Islamic calligraphy is the primary tool of Quranic expression, which is combined with a spiritual geometry, thus providing the viewers with aesthetic and cognitive frameworks. Many past kinds of research have emphasized the comprehensive explanation of Islamic calligraphy types and styles in general. However, little studies give concerns about the archetypal characteristics of the calligraphy in Muslim architecture. This paper aims to discuss Islamic calligraphy and architecture design based on the literature review and research published in the past few decades. The author adopted this method to investigate the most common types and styles of calligraphy in Muslim architecture that can be used for the archetypal profiling of Islamic calligraphy in public buildings. The analysis results are presented simultaneously with the information that characterizes the valuable calligraphy about its types, styles, and shapes, which are relevant to the Islamic architectural buildings. The research findings suggest further investigation of the calligraphy elements essential to sustain its harmony and aesthetic value in the Islamic architectural building concept.